Four Unrecorded Macrofungi from Mudeungsan National Park in Korea - Minseo Cho; Yeonjae Yoo; Sang Hyun Lee; Dae Young Kwon; Sun Lul Kwon; Jae-Jin Kim (한국균학회지)
Macrofungi are major decomposers in terrestrial ecosystems, acting as nutrient cyclers, wood decomposers, and plant symbionts. Despite their beneficial effects, the diversity of macrofungi is not as well understood as that of the flora and fauna. Mudeungsan National Park is one of the biggest National Parks in Southwestern Korea. We conducted surveys in Mudeungsan National Park from 2021 to 2023 to identify indigenous macrofungi. The collected specimens were identified based on morphological characteristics and molecular and phylogenetic analyses using the internal transcribed spacer (ITS), nuclear large subunit ribosomal DNA (nLSU), and translation elongation factor 1 gene (tef1) regions. Four species were identified as unrecorded in Korea: Anomoloma luteoalbum, Fibrodontia alba, Russula pallidula, and Schizocorticium parvisporum. In this study, we provide detailed morphological figures and phylogenetic trees to support the four unrecorded species in Mudeungsan National Park.